2013
DOI: 10.1007/s00277-013-1862-6
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility of clofarabine cytoreduction followed by haploidentical hematopoietic stem cell transplantation in patients with relapsed or refractory advanced acute leukemia

Abstract: Clofarabine is a novel purine nucleoside analogue with immunosuppressive and anti-leukemic activity in acute lymphoblastic and myeloid leukemia (AML, ALL). This retrospective study was performed to evaluate the feasibility and anti-leukemic activity of a sequential therapy using clofarabine for cytoreduction followed by conditioning for haploidentical hematopoietic stem cell transplantation (HSCT) in patients with non-remission acute leukemia. Patients received clofarabine (5 × 30 mg/m² IV) followed by a T cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
0
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 34 publications
(31 citation statements)
references
References 37 publications
1
28
0
2
Order By: Relevance
“…While VIRM mortality was significantly lower after the TCR/PTCY approach, IRM was not different. This may be due to the following reasons: First, as reported by our group previously for the TCR/PTCY haplo-HSCT approach [20,21], invasive pulmonary aspergillosis caused severe morbidity and mortality in our patients undergoing a second TCR/PTCY haplo-HSCT, while virus infection played a minor role, and immune reconstitution proved to be favorable using PTCY. Second, probably a high dosage of ATG promoted the development of PTLD in the cTCR/ TCD group, but consequent preemptive management of EBV reactivation and adoptive immunotherapy with EBV-specific T cells were available for patients of the cTCR/TCD group.…”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…While VIRM mortality was significantly lower after the TCR/PTCY approach, IRM was not different. This may be due to the following reasons: First, as reported by our group previously for the TCR/PTCY haplo-HSCT approach [20,21], invasive pulmonary aspergillosis caused severe morbidity and mortality in our patients undergoing a second TCR/PTCY haplo-HSCT, while virus infection played a minor role, and immune reconstitution proved to be favorable using PTCY. Second, probably a high dosage of ATG promoted the development of PTLD in the cTCR/ TCD group, but consequent preemptive management of EBV reactivation and adoptive immunotherapy with EBV-specific T cells were available for patients of the cTCR/TCD group.…”
Section: Discussionmentioning
confidence: 68%
“…In the TCR/PTCY setting, conditioning consisted of fludarabine and cyclophosphamide plus either TBI or melphalan, or treosulfan, alone or in combination with etoposide [20,21]. The graft source was unstimulated bone marrow or unmanipulated G-CSF-mobilized PBSCs on day 0; GvHD prophylaxis consisted of high-dose PTCY (50 mg/kg on days +3 and +4), followed by tacrolimus and mycophenolate mofetil (MMF), each starting at day +5 after transplantation [17].…”
Section: Preparative Regimenmentioning
confidence: 99%
“…The others series reporting the results of PT-Cy Haplo-SCT in the specific fields of AML or MDS included few patients (18)(19)(20)(21)(22)(23)(24)(25), with various proportion of refractory diseases (36-100%). [25][26][27] They found a PFS ranging from 39 to 72%. More recently, Bacigalupo et al reported promising results in AML and MDS, especially when Haplo-SCT was performed in CR1.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to HLA-matched transplantation administering clofarabine immediately after BU for conditioning in patients with non-remission malignant haematological diseases, 11 severe toxicities were less common, but are comparable to those of the T-cell-replete sequential therapy haplo-approach in nonremission acute leukaemia. 12 NRM was acceptable and in the lower end of the range (15-41%) described for RIC HLA-matched 3,29-34 and T-cell-replete haplo-HSCT performed mostly in chemo-sensitive, less aggressive lymphoma without active disease at the time of transplant. 15,32 There is some evidence of a GVL effect after RIC transplantation in aggressive NHL, 2,4,24,32 but this effect can take several months to become apparent.…”
Section: Discussionmentioning
confidence: 96%
“…7,8 Clofarabine has shown significant anti-tumour activity as a single agent in the treatment of NHL, including rituximabrefractory patients, 9,10 and was feasible and effective in HLA-matched and mismatched allo-HSCT. [11][12][13][14] Furthermore, T-cell-replete HLA-haploidentical transplantation using high-dose CY for post-grafting immunosuppression is reported to be associated with low rates of non-relapse mortality (NRM), and favourable results in the treatment of lymphoma have been observed. 8,15,16 Therefore, sequential therapy comprising clofarabine and T-cell-replete HLA-haploidentical transplantation seemed to be an attractive concept in the treatment of advanced NHL.…”
Section: Introductionmentioning
confidence: 99%